The Influence Workload, Motivation, and Work Environment On Employee Performance In CV. Djayadipa Yogyakarta - Fika Uswatun Khasanah; Asteria, Beta (University of Darussalam Gontor, 2024)
Performance serves as a measure of an employee's capability to fulfill their duties. This achievement can be affected by both internal and external factors. The purpose of this study is to identify the elements that affect employee performance at CV. Djayadipa, which is influenced by workload, motivation for the job, and the workplace environment. The data collection relied on primary data sources. The analysis utilized methods such as Multiple Linear Regression, Validity, Reliability, Multicollinearity, and Product Moment Correlation. A survey featuring a Likert scale for measurement accompanied by a sample group of 37 participants was employed to gather the information. The sampling approach was executed quantitatively. The results of the study revealed that (1) the Simultaneous Test showed that the performance of employees was affected by the factors of workload, motivation, and the work environment. (2) There was a slight negative impact of workload on employee performance. (3) Work motivation positively and significantly influenced employee performance metrics. (4) The workplace had a negative and minimal effect on employee performance characteristics.